Adenocarcinoma of the pigmented ciliary epithelium. (11th July 2014) - Sukeda, Aoi; Mori, Taisuke; Suzuki, Shigenobu; Ochiai, Atsushi
Abstract : Adenocarcinoma of the pigmented ciliary epithelium is an exceptionally rare eye tumour, with only a few cases reported to date. We encountered such a case in a 50-year-old woman who reported seeing floaters in her right eye. Fundus examination and MRI revealed an elevated lesion located in the ciliary body compressing the lens. The ciliary body was resected under the diagnosis of ciliary adenoma. On histological examination, the tumour exhibited epithelial features with glandular formation and moderate nuclear pleomorphism. The tumour invaded the subepithelial stroma of the ciliary body. Immunohistochemical findings were positive for cytokeratin OSCAR, AE1/AE3, CK7, EMA, S100, Melan A, HMB45, and microphthalmia-associated transcription factor.